Optimal design of turbines taking into consideration the mode of operation - Boiko, A. V.; Govorushchenko, Yu. N.; Usaty, A. P.; Rudenko, A. S. (My University, 2009)
The technique of turbines parameters optimization taking into consideration a variable mode of their operation has been developed. Block-hierarchical representation of design process is used. The hierarchy of local optimization problems is organized by a functional sign and realized in a common information space. The structure of optimization technique is shown, and also the analysis of the data streams uniting these problems in unified process of optimal design is resulted. By means of the developed technique optimal design of the 4-stage turbine expander with rated power 4 MW has been performed. Results of the design are presented and analyzed.
Keywords: turbine; optimal design; mode of turbine operation; operating mode; cylinder; flow path; economic losses; design of experiment; formal macromodel; CAD; турбіни; оптимальне проектування; режим експлуатації турбін; циліндри; проточна частина; планування експерименту (DOE); САПР